Model Kegiatan Transisi Pendidikan Anak Usia Dini (PAUD) ke Sekolah Dasar (SD) Berdasarkan enam Aspek Pondasi Transisi di Kota Malang - Wardatus Sholihah; Moezenatus Sholiha; Putri Septianingrum; Dessy Putri Wahyuningtyas (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
This qualitative research aims to determine the effectiveness of the transition program from early childhood education (PAUD) to elementary school (SD) in Malang, based on six fundamental aspects. Through a survey of teachers and principals, this study explores the model, implementation process, and factors influencing the program's transition. Data were collected using a questionnaire and analyzed to assess the extent to which six basic aspects are included in the transition process. Researchers point out that despite efforts to combine these aspects, challenges such as lack of teacher training, inconsistent implementation, and emphasis on academic achievement still remain. This study highlights the need for a more holistic approach to transition programs that prioritizes social-emotional development, critical thinking, and a love of learning. The recommendations include providing professional development to teachers on six basic aspects, fostering collaboration between PAUD and SD, and involving parents in the transition process.